Creative industries in Wrocław in questions and answers. Research report - Błaszczyk, Mateusz; Banaszak, Ewa; Kajdanek, Katarzyna; Pluta, Jacek (Instytut Socjologii Uniwersytet Wrocławski)
The report presents results of a quantitative research on creative industries in Wrocław and how they are linked with the project of European Capital of Culture Wrocław 2016. The structure of creative industries in Wroclaw, its economic situation and prospects as well the assessment of local policies and general economic environment facilitating development of cultural economy in Wrocław are described in the report. Moreover, the document contains data on the involvement of local creative businesses in the organization of ECoC Wrocław 2016 and on the perceived advantages of such commitment for the city, its inhabitants and for the businesses.
Keywords: creative industries; European Capital of Culture; urban economy; Wrocław